Fishery of sciaenids off Veraval with special reference to growth, mortality and stock assessment of Otolithes cuvieri (Trewavas, 1974) - Manojkumar, P P (Indian Journal of Fisheries, 2011)
Sciaenids form an important demersal finfish resource off Veraval and contributeabout 12 % to the total marine landings. They are exploited mainly by trawlsand gillnets with an annual average landing of 9086 t and 323 t respectivelyduring 1986-95. Nearly 16 species contribute to the sciaenid fishery of which,Otolithes cuvieri and Johnius glaucus contributed 52.6% and 13.8 % respectively.In gill net seven species contribute to the landings, dominated by Otolithes cuvieriand Protonibea diacanthus. The peak landing of sciaenids was noticed inSeptember and January. Studies on O. cuvieri revealed that there was nosignificant difference in the length weight relationship between the sexes, andhence a common regression was fitted as Log W = -4.4632 + 2.9701 Log L(r=0.9036). The asymptotic length (Lô€ƒ) and growth coefficient (K) were estimatedas 382 mm and 0.89 y-1 respectively. O. cuvieri grows to 225, 317, 354, 371 and382 mm at the end of 1st, 2nd, 3 rd, 4th and 5th years. The fishery mainlyconsisted of 0 and 1 year classes. The average instantaneous rates of total,natural and fishing mortalities were 2.86 y-1, 0.81 y-1 and 2.05 y-1 respectively.The length at first capture was 148 mm at which the age works out to be 0.5year. The exploitation ratio is higher than the Emax estimated indicating thatthe resource is overexploited. In view of the heavy fishing pressure, there is aneed for reducing the fishing effort to sustain the fishery.